Antibiotic Resistance Trends in ESKAPE Pathogens Isolated at a Health Practice and Research Hospital: A Five-Year Retrospective Study - Orhan, Zerife; Kirişci, Özlem; Doğaner, Adem; Altun, Mehzat; Küçük, Burak; Aral, Murat (The Journal of Infection in Developing Countries, 2024)
Introduction: Antimicrobial resistance remains a global threat with increasing morbidity and mortality rates. The aim of this study was to identify the antimicrobial resistance trends among ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) isolated from clinical samples at a Health Practice and Research Hospital over five years. Methodology: Microbiological diagnosis utilized classical culture methods and automated systems. Antimicrobial susceptibility analysis was conducted using BD Phoenix, adhering to European Committee on Antimicrobial Susceptibility Testing (EUCAST) standards. Results: A total of 15,272 clinical strains of ESKAPE pathogens were identified in this study. The most frequently isolated pathogens among ESKAPE were K. pneumoniae (3.938, 27.79%), Acinetobacter baumannii (3,013, 19.73%) and Enterococcus faecium (2,966, 19.24%). Bacterial strains were isolated predominantly from urine (3,263, 21.37%), followed by blood cultures (3,099, 20.29%). ESKAPE pathogens were most commonly found in internal intensive care units (4,758, 31.16%), followed by surgical intensive care units (4,000, 26.19%). Reduced resistance rates were observed for most antibiotics against Enterococcus faecium and Staphylococcus aureus. The vancomycin resistance rate for Enterococcus faecium was 18.48%, and the methicillin resistance rate for Staphylococcus aureus was 44.87%. A concerning trend of increasing antimicrobial resistance was noted in Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. Conclusions: The alarming rise in antimicrobial resistance among Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae is a significant concern. The high rates of antimicrobial resistance observed in ESKAPE pathogens underscore the urgent need for improvement in antimicrobial stewardship and infection prevention and control programs.